2001
DOI: 10.1111/j.1479-828x.2001.tb01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal counselling, resuscitation practices and attitudes among Australian neonatologists towards life support in extreme prematurity

Abstract: A questionnaire survey of Australian neonatologists was conducted to ascertain their antenatal counselling and resuscitation practices, and attitudes towards life support in the extremely preterm infant. This study showed that in antenatal parental counselling, whether a paediatrician was given the opportunity to participate depends on the gestation at the time of the threatened preterm delivery The counselling employed almost invariably covered mortality and morbidity. The obstetrician's opinion was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…19,29,30,32 The results from this study show that the adequacy of parent counseling differs by center and topic. Discussions of morbidity and mortality adequately addressed the information needs of the majority of parents in only 5 of 9 centers.…”
Section: Counselingmentioning
confidence: 78%
See 3 more Smart Citations
“…19,29,30,32 The results from this study show that the adequacy of parent counseling differs by center and topic. Discussions of morbidity and mortality adequately addressed the information needs of the majority of parents in only 5 of 9 centers.…”
Section: Counselingmentioning
confidence: 78%
“…Although several hospital-based studies and surveys have detailed physicians' attitudes and practices on life support and end-of-life decisions for premature infants, 19,29,30,[33][34][35][36]45,46 only a few have addressed parents' perspectives of counseling and decision-making. 42,45,47 To our knowledge, this is the first cross-cultural study of counseling and resuscitation decision-making from the perspective of parents of VLBW premature infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Similarly, Munro et al reported that a neonatologist's treatment plan was more likely to be altered to accommodate parents' wishes at 23 or 24 weeks' gestation than at 22 or 25 weeks. 21 Respondents in our study did vary, however, in their attitudes toward parental wishes. A significant minority (24%) reported that when the benefit of treatment is uncertain, they would initiate resuscitation regardless of parental wishes and make future treatment decisions based on the infant's condition.…”
Section: Discussionmentioning
confidence: 90%